Facile approach to prepare pH and redox-responsive nanogels via Diels-Alder click reaction - C. M. Q. Le; X. T. Cao; T. T. K. Tu; Y-S. Gal; K. T. Lim (eXPRESS Polymer Letters, 2018)
A novel pH and redox responsive system of sub-100 nm nanogels was prepared by arm-first approach via Diels-Alder click reaction. First, well-defined poly(ethylene glycol)-block-poly(styrene-alt-maleic anhydride) (PEG-b-PSM) was synthesized and subsequently functionalized with furfuryl amine, leading to the formation of the dual-functional block copolymer of PEG-b-PSMf. The furfuryl groups in the PSMf block were employed to incorporate a redox-responsive linkage and the carboxylic acid moieties generated through functionalization acted as a pH-responsive part. The Diels-Alder click reaction between a bismaleimide crosslinker and PEG-b-PSMf was conducted at 60 °C, affording star-like nanogel structures. Doxorubicin, a model anticancer drug, was loaded into to the core of the nanogels primarily by the ionic interaction with carboxylates of core blocks and a highest drug loading capacity of 38.1% was obtained. Furthermore, the in vitro profile showed a low release percentage (11.2%) of DOX at PBS pH 7.4, whereas a burst release (62%) at pH 5.0 in the presence of 10 mM glutathione, indicating the effective pH and redox responsive characteristic of the PEG-b-PSMf nanogels.